Opinion on Distribution Nature of NEPSE Return: A Qualitative Analysis - Rashesh Vaidya; Dilli Raj Sharma; Jeetendra Dangol (Social Science Studies, 2023)
The paper conducted a qualitative analysis among the Nepalese econophysicist-cum-investors regarding the opinions on the investment environment of the Nepalese stock market (NEPSE) and the challenges they have been facing while going for an investment decision. The paper has also gotten opinions on the screening process from the NEPSE from the interviewees and their opinion on the distribution nature of the return from the market. The paper followed the grounded theory to come with certain theories from the opinions. The paper found that the strong fundamentals of the listed companies were a concern for the interviewees. Similarly, wrong information and trading procedures were seen as concerns among interviewees. The paper found from interviews that the published financial reports of the listed companies helped in screening the shares to make a better portfolio among the Nepalese econophysicist-cum-investors. Finally, in the context of the distribution nature of NEPSE return, most interviewees viewed that the return follows the normal distribution. The interviewees viewed that the market return follows the power-law when the bull-run continues, backed by the extreme magnitude of trade volume as well as the perfect political and economic condition of the nation. They also linked the nature of return distribution with the behavioral factors of the investment decision process.